Overview of Parents' Psychosocial Problems due to The Use of Gadgets in School-Age Children during The Covid-19 Pandemic - Abdul Haris; Eka Budiarto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background: COVID-19 managed to interfere the world with its presence at the end of 2019. The impact of the COVID-19 pandemic occurred in various fields such as social, economic, tourism and education. A huge impact is felt in the education sector where the learning process must be done online and accessed via gadgets. This situation makes the intensity of the use of gadgets in school students will increase because the learning process must continue, where for now the phenomenon of using gadgets among school-age children continues to increase, this certainly has an impact on children and the negative impact is dominant. Facing conditions like this makes some parents experience psychosocial problems. Objective: This study aims to identify the psychosocial problems of parents due to the use of gadgets in school-age children during the COVID-19 pandemic Sample: Total sampling technique in selecting research subjects with a sample of 157 parents/guardians of students at SDN 02 Mayangan, Pekalongan Regency. Methods: This research is a quantitative research using analytical description research. Results: The results showed several psychosocial problems experienced by parents, including mental emotional disorders as much as 54.8%, addictive substance abuse as much as 3.2%, psychotic symptoms as much as 24.8% and PTSD as much as 44.6%. Conclusion: Psychosocial problems have been proven to be experienced by parents whose children are undergoing the online primary school level learning process during the COVID 19 pandemic.